2018
DOI: 10.1002/jcb.27912
|View full text |Cite
|
Sign up to set email alerts
|

miR‐32 promotes esophageal squamous cell carcinoma metastasis by targeting CXXC5

Abstract: MicroRNA‐32 (miR‐32) functioned as a tumor oncogene in some cancer, which control genes involved in important biological and pathological functions and facilitate the tumor growth and metastasis. However, the role of miR‐32 modulates esophageal squamous cell carcinoma (ESCC) malignant transformation has not been clarified. Here, we focused on the function and the underlying molecular mechanism of miR‐32 in ESCC. Results discovered a significant increased expression of miR‐32 in ESCC tissues and cells. Downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Surgery alone remains the standard treatment for patients at the early stage (3). However, ESCC is typically diagnosed at an advanced stage, due to a lack of clinical diagnostic techniques (4). Lymph node metastasis occurs in ~40% of patients with ESCC, which results in poor prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Surgery alone remains the standard treatment for patients at the early stage (3). However, ESCC is typically diagnosed at an advanced stage, due to a lack of clinical diagnostic techniques (4). Lymph node metastasis occurs in ~40% of patients with ESCC, which results in poor prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…The average time gap between formation of two C−C bonds varies from 11 fs in the gas phase, to 17 fs in Truhlar's implicit solvent model (SMD), and to 25 fs in QM/MM calculations, indicative of the stabilization of dynamical zwitterionic species by explicit water molecules. We further tested the reaction with QM/QM′(PM3), which also shows the hydrogen bonding enhancement effects.…”
Section: Dynamics Of Pericyclic Reactions In the Gas Phase Solution mentioning
confidence: 99%
“…In total, ~50% of the annotated miRNAs are located at fragile sites in the genome of the tumor, indicating that miRNAs play a vital role in the process of cancer (Mao et al, ). A higher expression has been reported for miR‐21, miR‐16, miR‐25, and miR‐199 in esophageal cancer tissues compared with adjacent tissues, whereas a lower expression was found for miR‐133a, miR‐138, miR‐195, and miR‐200b (Liu et al, ; Zhang et al, ). The present study found a low expression of miR‐126‐5p in esophageal cancer tissues and cells, suggesting that miR‐126‐5p may play an important inhibitory role in the occurrence and development of esophageal cancer as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%